Improvement of accuracy and speed of a commercial AFM using Positive Position Feedback control - Mahmood, Iskandar Al-Thani; Moheimani, S.O. Reza (2009)
The atomic force microscope (AFM) is a device capable of generating topographic images of sample surfaces with extremely high resolutions down to the atomic level. It is also being used in applications that involve manipulation of matter at a nanoscale. Early AFMs were operated in open loop. As a result, they were susceptible to piezoelectric creep, thermal drift, hysteresis nonlinearity and scan-induced vibration. These effects tend to distort the generated image. The distortions are often minimized by limiting the scanning speed and range of the AFMs. Recently a new generation of AFMs has emerged that utilizes position sensors to measure displacements of the scanner in three dimensions. These AFMs are equipped with feedback loops that work to minimize the adverse effects of hysteresis, piezoelectric creep and thermal drift on the obtained image using standard PI controllers. These feedback controllers are often not designed to deal with the highly resonant nature of an AFM's scanner, nor with the cross-coupling between various axes. In this paper we illustrate the drastic improvement in accuracy and imaging speed that can be obtained by proper design of a feedback controller. Such controllers can be incorporated into most modern AFMs with minimal effort since they can be implemented in software with the existing hardware.